The history of the creation of the poem "Requiem" by A.A. Akhmatova (Zien Journal of Social Sciences and Humanities, 2023)
This article discusses the history of the creation of the poem "Requiem" by the author of the twentieth century. Anna Akhmatova, her personal notes, memoirs of friends who helped her in creating the poem, collection of essays, first edition in the Munich magazine, portrait and sound recording